2022
DOI: 10.1136/bmjopen-2022-063395
|View full text |Cite
|
Sign up to set email alerts
|

From hearing to seeing: medical dispatchers’ experience with use of video streaming in medical emergency calls − a qualitative study

Abstract: ObjectivesVideo streaming has recently been introduced as an additional tool for communication between medical dispatchers and caller. Research implies that video streaming may be a useful tool for the dispatchers, but more knowledge is needed. With this study, we wanted to explore how the dispatchers experience using video streaming as an additional tool in medical emergency calls.DesignAn explorative, qualitative study using semi-structured focus group interviews.SettingTwo emergency medical communications c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Findings from the inner-city sub-study, which will be reported in full elsewhere, supported the need for governance around if/when/how video livestreaming should be used. Similar conclusions have been reported in the wider literature [ 14 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings from the inner-city sub-study, which will be reported in full elsewhere, supported the need for governance around if/when/how video livestreaming should be used. Similar conclusions have been reported in the wider literature [ 14 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Most of these studies have been simulation-based [ 11 13 ] with few studies in real-life settings. Evidence suggests that use of video livestreaming from the scene may impact on decision-making [ 8 , 14 ] and enable faster and more accurate decisions about EMS resources to be tasked [ 3 ]. To our knowledge, two real-life studies have focussed on the impact of video livestreaming from callers [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 6 This potential reduction in overestimation or underestimation of the severity was also reported in a qualitative study of EMCC operators’ experiences with video, where some of the operators believed that video could contribute to better resource utilisation. 5 Thus, it would be tempting to develop a guideline to increase the use of video. However, this would be challenging to implement as it seems that was the operators’ subjective need that triggered the decision to use video and not any specific symptom or condition.…”
Section: Discussionmentioning
confidence: 99%
“…4 This was in accordance with our findings ( table 2 ), and it seems to suggest that the callers were perceived to particularly overestimate bleeding amount and injuries, and thus, operators found great utility in video. According to Idland et al , 5 several operators perceived video as a reassurance for their own decisions. This is consistent with our findings, where operators felt that video confirmed that the patient’s severity matched what they had perceived during the phone call.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation